2020
DOI: 10.1159/000511151
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Pallidal Stimulation with Directional Leads for Primary Focal Lingual Dystonia

Abstract: There have been limited studies regarding stereotactic and functional neurosurgery for lingual dystonia. Here, we report a patient with primary lingual dystonia who showed significant improvement after bilateral deep brain stimulation (DBS). A 42-year-old woman presented with a 5- to 6-year history of tongue protrusion; however, she lacked a significant medical or medication history before onset. She presented with gradually worsening symptoms and was diagnosed with idiopathic lingual dystonia. Her tongue was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Most experts believed that mainly patients with well-established indications, such as PD, tremor and dystonia would benefit most from directionality. This is very much in line with the literature so far, where most published studies are on PD and tremor ( Bruno et al, 2021 ; Shao et al, 2020 ; Rebelo et al, 2018 ; Schnitzler et al, 2022 ), with only a small number of case reports or small case series on dystonia, pain or psychiatric diseases ( Abel et al, 2021 ; Asahi et al, 2021 ; Krüger et al, 2021c ; Coenen et al, 2022 ; Lopez et al, 2021 ), and no studies on depression or epilepsy.…”
Section: Discussionsupporting
confidence: 87%
“…Most experts believed that mainly patients with well-established indications, such as PD, tremor and dystonia would benefit most from directionality. This is very much in line with the literature so far, where most published studies are on PD and tremor ( Bruno et al, 2021 ; Shao et al, 2020 ; Rebelo et al, 2018 ; Schnitzler et al, 2022 ), with only a small number of case reports or small case series on dystonia, pain or psychiatric diseases ( Abel et al, 2021 ; Asahi et al, 2021 ; Krüger et al, 2021c ; Coenen et al, 2022 ; Lopez et al, 2021 ), and no studies on depression or epilepsy.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, only three published case reports have discussed bilateral GPi-DBS for OMD, all of which were categorized as lingual dystonia. Chung et al [20] and Asahi et al [22] reported symptomatic improvements in lingual dystonia following bilateral GPi-DBS in two cases and one case, respectively. In patients with OMD, the unique neuroanatomical characteristics of bilateral innervation in each side of the stomatognathic system may complicate the application of conventional DBS compared to that in patients with focal dystonia of the limbs, as previous studies have reported that sufficient effects are sometimes difficult to obtain with interventions targeting the unilateral hemisphere.…”
Section: Treatment Options For Omdmentioning
confidence: 99%
“…Several case reports from the past two decades have described the use of DBS of the bilateral Gpi for the treatment of lingual dystonia [19][20][21][22]. This bilateral approach is based on the neurophysiological principle that tongue movements are regulated by the bilateral central regions through the corticobulbar tract, which differs from the contralateral regulation of the limbs (Figure 1).…”
Section: Introductionmentioning
confidence: 99%